2016
DOI: 10.12693/aphyspola.129.1187
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Tuning of MEH-PPV for Organic Electronic Applications

Abstract: In this report, a doped semiconducting ink consisting of a blended poly [2-methoxy-5-(2'-ethyl-hexyloxy)-1,4-phenylene vinylene] (MEH-PPV) with aluminium-tris (8-hydroxychinolin) (Alq3) and diluted in toluene is formulated. The intentional doping with the electron transport nanoparticle Alq3 results in an additional band gap state of the hole transport MEH-PPV polymer and reduction of the switch on voltage of the organic LED display. Doping is probed at room temperature with photoluminescence spectroscopy. Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This indicates that, as the concentration of acceptor increases in the solution, more efficient radiationless energy transfer takes place between the donor–acceptor pair. In the emission spectrum of the donor–acceptor solution, we could not observe any new emission band, which rules out the formation of exciplex of AlQ 3 -MEH-PPV in chloroform solution, which is observed in their blend …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…This indicates that, as the concentration of acceptor increases in the solution, more efficient radiationless energy transfer takes place between the donor–acceptor pair. In the emission spectrum of the donor–acceptor solution, we could not observe any new emission band, which rules out the formation of exciplex of AlQ 3 -MEH-PPV in chloroform solution, which is observed in their blend …”
Section: Resultsmentioning
confidence: 64%
“…On increasing acceptor concentration, it is also evident from these spectra that In the emission spectrum of the donor−acceptor solution, we could not observe any new emission band, which rules out the formation of exciplex of AlQ 3 -MEH-PPV in chloroform solution, which is observed in their blend. 6 Further, as we increase the amount of acceptor in the solution, the contribution of energy migration due to acceptor−acceptor interaction also increases. Therefore, a successive red shift in the emission maxima corresponding to the acceptor appears on increasing the concentration of acceptor.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The existence of NPs can change the dynamics of polymers and therefore shifts the glass transition temperature [14] and slows down the diffusion of polymer chains [15]. Recently, the dynamics of polymer melts and concentrated polymer solutions have been studied intensively by experiments [16,17], theory and computer simulations [18][19][20][21]. It was found that the properties of polymers would be influenced by many parameters, such as size, shape, and concentration of NPs and interaction strength between polymer and NP [10].…”
Section: Introductionmentioning
confidence: 99%